Relationship between talofibular impingement and increased talar tilt in incongruent varus ankle osteoarthritis. (6th December 2021) - Kyung, Min Gyu; Cho, Yun Jae; Lee, Junpyo; Lee, Wonik; Kim, Dae-Yoo; Lee, Dong-Oh; Lee, Dong Yeon
Purpose: This study aimed to evaluate the relationship between talofibular impingement and increased talar tilt in incongruent varus ankle osteoarthritis.Methods: Incongruent varus ankle osteoarthritis was defined as a talar tilt of more than 4° on standard ankle anteroposterior radiographs. We retrospectively reviewed 30 patients with unilateral incongruent varus ankle osteoarthritis with normal alignment of the contralateral ankle. All patients underwent bilateral weightbearing computed tomography and standing plain radiographs. The talar tilt and the distance between the talar lateral process and lateral malleolar tip were measured from a standing ankle anteroposterior radiograph of both sides. Talar and fibular spurs were assessed on the coronal and axial views of weightbearing computed tomography. After simulating the correction of the talar tilt in varus ankle osteoarthritis, talofibular bony impingement was reassessed.Results: On the varus side, the distance between the talar lateral process and the lateral malleolar tip was significantly shorter than that on the contralateral side ( p < .001). Talar spur was present in the varus side of all 30 patients on the axial view of weightbearing computed tomography and in the control side of 10 patients. After the simulation of talar tilt correction, talofibular impingement (overlap) occurred in all 30 patients with a larger extent in the severe talar tilt subgroup ( p < .001).Conclusion: Talofibular impingement by lateral gutter osteophytes is closely related to increased talar tilt in patients with incongruent varus ankle osteoarthritis. Therefore, lateral gutter osteophytes should be resected to stabilize mortise and improve clinical outcomes.